Nutrient Recovery From the Liquid Fraction of Digestate by Clinoptilolite. Issue 6 (10th May 2017) - Kocatürk‐Schumacher, Nazlı Pelin; Bruun, Sander; Zwart, Kor; Jensen, Lars Stoumann
Abstract : The direct application of the liquid fraction of biogas digestate to agricultural fields as a fertilizer may result in practical and environmental problems. Concentrating nutrients onto clinoptilolite and subsequently using clinoptilolite as a fertilizer could be an alternative solution for the management of nutrients in the liquid fraction of digestate. In this study, the use of clinoptilolite to recover ammonium, potassium, and orthophosphate from the liquid fraction of digestate was investigated. The optimal preconditioning of clinoptilolite and the optimal initial nutrient‐to‐clinoptilolite loading ratio was determined to achieve the highest nutrient removal efficiency. Preconditioning of clinoptilolite had no significant effect on the total ammonium and potassium removal from the liquid fraction of digestate. An increase in the initial loading ratio significantly increased nutrient concentrations on the clinoptilolite, but decreased nutrient removal efficiencies from the liquid fraction of digestate: removal efficiencies ranged from 40 to 89% for ammonium, 37 to 78% for potassium, and 64 to 80% for orthophosphate at various initial loading ratios. Overall, the increase in the concentration of nutrients on the clinoptilolite was relatively low, however, nutrients could be removed from the liquid fraction of digestate with high removal efficiencies. This indicated that the use of clinoptilolite could be a solution for improved management and utilization of the liquid fractions of digestate. Abstract : This study examines the ability of clinoptilolite to remove nutrients (N, P, and K investigated) from the liquid fraction of digestate. Nutrients can be removed with high removal efficiencies, which results in concentration of nutrients on the clinoptilolite. This would allow for volume reduction, which provides savings on storage and transport of liquid fractions of digestate.